Lithium ion battery silicon negative electrode with optimized alloying array transition layer and preparation method of lithium ion battery silicon negative electrode

Through the preparation method of alloyed array transition layer optimization, the problem of volume change and low conductivity of silicon negative electrode during the cycle of lithium-ion battery is solved, and better electrochemical performance and adhesion strength are achieved.

CN119517940APending Publication Date: 2025-02-25SUZHOU VOCATIONAL UNIVERSITY (SUZHOU OPEN UNIVERSITY)
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411661690.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The silicon negative electrode changes dramatically during the cycle of lithium-ion battery and has low conductivity, resulting in poor electrochemical performance, and its adherence to the current collector is not firmly strong and easy to fall off.

Method used

Using the preparation method of alloyed array transition layer optimization, the copper sheet is anodic oxidized by potassium hydroxide solution to form a copper hydroxide nanowire array, and then annealed under a mixed atmosphere of argon and hydrogen and coated with silicon active substances by magnetron sputtering to finally form a nanowire array of Cu3Si alloy.

Benefits of technology

The electrochemical performance of the silicon negative electrode is improved, the adhesion strength to the current collector is enhanced, the shedding phenomenon is reduced, and the performance under high current density is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119517940A_ABST
    Figure CN119517940A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of preparation of negative electrode materials, and particularly relates to a lithium ion battery silicon negative electrode with an optimized alloying array transition layer and a preparation method of the lithium ion battery silicon negative electrode. A potassium hydroxide solution is used as an electrolyte, a copper foil is placed on a constant voltage source to be subjected to anodic oxidation, a Cu (OH) 2 nanowire array with the surface evenly growing is obtained, annealing treatment of argon and hydrogen mixed gas is conducted before a silicon active substance is coated through magnetron sputtering, and the Cu nanowire is obtained through reduction. After the Si active material layer is coated by magnetron sputtering, the whole electrode is subjected to annealing treatment, so that a Cu3Si alloy is generated at the interface of Cu and Si, and the contact strength and the conductive efficiency of the Cu and the Si are enhanced. According to the invention, the problem that the silicon negative electrode is not firmly adhered to the current collector and is easy to fall off from the current collector to cause power loss in the battery circulation process under the condition of violent volume change is solved. The reaction specific surface area is increased through the three-dimensional nanowire array structure, and the performance of the silicon negative electrode under the large current density is enhanced through the transition layer of the copper-silicon alloy.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of negative electrode material preparation, and specifically relates to a lithium ion battery silicon negative electrode with an optimized alloy array transition layer and a preparation method thereof. Background Art

[0002] In order to achieve a higher energy density for lithium-ion batteries, it is necessary to develop more efficient positive and negative electrode materials. Compared with the currently commercialized graphite negative electrode materials, the mass specific capacity of silicon negative electrode materials is about 10 times that of the latter, so it has received a lot of attention. However, the drastic volume changes of silicon negative electrodes during the cycle and the low electrical conductivity of silicon materials are subject to considerable application constraints. Researchers have made a series of improvements to silicon negative electrodes through nano-sizing, silicon-carbon composites, and porosification, which have enabled them to advance step by step on the road to application.

[0003] In 2018, researchers from Georgia Institute of Technology and the Beijing Institute of Nanoenergy and Nanosystems of the Chinese Academy of Sciences immersed copper foil in a solution of sodium hydroxide and ammonium persulfate to grow copper hydroxide nanowires on the surface. They also used magnetron sputtering and to prepare a core-shell structure nanowire negative electrode material Cu(OH)2@Si with a core of copper hydroxide and a shell of silicon. They then annealed and reduced it with an argon-hydrogen mixture to prepare a Cu@Si core-shell structure nanowire negative electrode material.

[0004] This method requires two chemicals and a reaction time of up to 48 hours in the process of growing nanowire structures on the surface of copper foil, and the reaction speed is slow. In the process of transforming from Cu(OH)2@Si to Cu@Si structure, the hydrogen and oxygen elements contained in the core Cu(OH)2 are difficult to completely escape from the outer silicon, which will affect the electrochemical performance. Summary of the invention

[0005] In order to solve the above-mentioned technical problems, this application provides the following technical solutions:

[0006] The present invention provides a method for preparing a lithium-ion battery silicon negative electrode with an optimized alloy array transition layer, comprising the following steps:

[0007] S11: connecting the pretreated copper sheet to the anode of a voltage source, connecting the platinum electrode to the cathode of a voltage source, and oxidizing the copper sheet in an aqueous solution of potassium hydroxide to obtain a copper hydroxide nanowire array;

[0008] S12: washing the copper hydroxide nanowire array with water and then drying it to obtain a Cu(OH)2NW sample;

[0009] S13: In an argon-hydrogen mixed atmosphere, the Cu(OH)2NW sample is heated to 380-420° C. and kept at this temperature for 1.5-2.5 h, and then cooled to obtain a CuNW sample;

[0010] S14: Under a protective atmosphere, magnetron sputtering the CuNW sample with a radio frequency power target for 0.8-1.2 hours, and then magnetron sputtering with a direct current target for 25-35 minutes to obtain a CuNW@Si@C sample; the radio frequency power target is selected from a polycrystalline silicon target, and the direct current target is selected from a graphite target;

[0011] S15: annealing the CuNW@Si@C sample under a protective atmosphere to obtain the lithium-ion battery silicon negative electrode with the alloyed array transition layer optimized.

[0012] Preferably, in step S11, the copper sheet is pretreated by ultrasonically cleaning with hydrochloric acid, water, acetone and ethanol in sequence, and then drying.

[0013] Preferably, the concentration of potassium hydroxide in the aqueous solution is 0.8-1.2 mol L -1 .

[0014] Preferably, in step S11, the output voltage of the voltage source during oxidation is 1-1.4V.

[0015] Preferably, in the argon-hydrogen mixed atmosphere, the volume proportion of hydrogen is 4-6%.

[0016] Preferably, in step S13, the heating rate is 4-6°C / min.

[0017] Preferably, in step S14, pre-sputtering is performed for 2-4 minutes before magnetron sputtering.

[0018] Preferably, in step S14, during magnetron sputtering, the substrate rotation speed is 18-22 rpm, the working power of the RF power target is 80-120 W, and the working power of the DC target is 40-60 W.

[0019] Preferably, in steps S14 and S15, the protective atmosphere is argon atmosphere.

[0020] Preferably, in step S15, the annealing method is to heat up to 350-450°C and then naturally cool to room temperature (25±5°C); during annealing, the heating rate is 4-6°C / min.

[0021] The present invention also provides a lithium-ion battery silicon negative electrode with an optimized alloyed array transition layer prepared by the above preparation method.

[0022] The present invention solves the problem that the silicon negative electrode has a loose adhesion to the current collector when the volume changes dramatically during the battery cycle, and is easily detached from the current collector, resulting in electrical disconnection. At the same time, the three-dimensional nanowire array structure increases the reaction specific surface area, and the transition layer of copper-silicon alloy enhances the performance of the silicon negative electrode under high current density.

[0023] The technical solution of the present invention has the following advantages over the prior art:

[0024] In the process of preparing the nanowire array on the surface of the copper foil, the present invention uses potassium hydroxide solution as the electrolyte, and the copper foil is placed on a constant voltage source for anodization. In 10 minutes, a Cu(OH)2 nanowire array with uniform surface growth can be obtained. And before magnetron sputtering and coating the silicon active material, it is annealed with an argon-hydrogen mixture gas, and the Cu(OH)2 nanowires are easily and completely reduced to Cu nanowires. After the Si active material layer is coated by magnetron sputtering, the entire electrode is annealed to generate a Cu3Si alloy at the interface of Cu and Si to enhance the contact strength and conductivity of the two. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 Schematic diagram of the preparation process.

[0026] Figure 2 This is the electron microscope image of the Cu(OH)2NW sample.

[0027] Figure 3 This is the electron microscope image of the CuNW sample.

[0028] Figure 4 This is the electron microscope image of the CuNW@Si@C-400℃ sample.

[0029] Figure 5 This is a graph of the constant current battery cycling performance.

[0030] Figure 6 This is a battery rate performance diagram. DETAILED DESCRIPTION

[0031] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention.

[0032] Example 1

[0033] Step (1) Select a copper sheet with a circular shape, a thickness of 8 μm, and a diameter of 10 mm, and ultrasonically clean the copper sheet with dilute hydrochloric acid, deionized water, acetone, and anhydrous ethanol in sequence, and dry it for later use;

[0034] Step (2) Prepare 1 mol L -1 of potassium hydroxide solution;

[0035] Step (3) The constant voltage source is set to an output voltage of 1.2 V, the copper sheet dried in step (1) is connected to the anode of the voltage source, and a platinum electrode is connected to the cathode of the voltage source;

[0036] Step (4) placing the copper sheet and platinum electrode of the voltage source cathode and anode into the potassium hydroxide solution prepared in step (2) for anodic oxidation for 10 minutes, and forming a dense and uniform copper hydroxide nanowire array on the surface, and the sample is recorded as Cu(OH)2NW;

[0037] Step (5) remove the Cu(OH)2NW from the potassium hydroxide solution, rinse with deionized water, and dry for later use;

[0038] Step (6) Place the dried Cu(OH)2NW sample in step (6) into a tube furnace, introduce an argon-hydrogen mixed gas (hydrogen 5%), and heat at 5°C min -1 The temperature was raised to 400 °C at a rate of 1.5 °C and maintained for 2 h. After natural cooling, a copper nanowire array with reduced surface was obtained, and the sample was recorded as CuNW.

[0039] Step (7) In the magnetron sputtering machine, the CuNW sample is fixed on the sample stage to form a sputtering substrate, and the sample substrate speed is 20 rmin. -1 To ensure the uniformity of sputtering, a polysilicon target was placed at the RF power target position with a working power of 100W, and a graphite target was placed at the DC power target position with a working power of 50W. The sputtering chamber was evacuated to 5E-4Pa, and high-purity argon gas was introduced until the pressure was 0.4Pa, and pre-sputtering was performed for 3 minutes. During the formal sputtering, the RF target worked for 1 hour, and then the DC target worked for 30 minutes. The sample was recorded as CuNW@Si@C;

[0040] Step (8) annealing the sample CuNW@Si@C obtained in step (7) in an argon environment of a sputtering chamber at 5°C min -1 The temperature was raised to 400℃ and then cooled naturally to obtain a Cu3Si alloy nanowire array, which was named CuNW@Si@C-400℃.

[0041] The electrochemical performance of the CuNW@Si@C-400℃ negative electrode sample prepared in this example was tested. -1 The specific capacity remains at 1109 mAh g after 1000 cycles at a current density of -1 , at 10Ag -1 At a current density of 1.34 W, the specific capacity remains at 491 mAh g -1 .

[0042] Example 2

[0043] Step (1) Select a copper sheet with a circular shape, a thickness of 8 μm, and a diameter of 10 mm, and ultrasonically clean the copper sheet with dilute hydrochloric acid, deionized water, acetone, and anhydrous ethanol in sequence, and dry it for later use;

[0044] Step (2) Prepare 0.8 mol L -1of potassium hydroxide solution;

[0045] Step (3) The constant voltage source is set to an output voltage of 1V, the copper sheet dried in step (1) is connected to the anode of the voltage source, and a platinum electrode is connected to the cathode of the voltage source;

[0046] Step (4) placing the copper sheet and platinum electrode of the voltage source cathode and anode into the potassium hydroxide solution prepared in step (2) for anodic oxidation for 8 minutes, forming a dense and uniform copper hydroxide nanowire array on the surface, and the sample is recorded as Cu(OH)2NW;

[0047] Step (5) remove the Cu(OH)2NW from the potassium hydroxide solution, rinse with deionized water, and dry for later use;

[0048] Step (6) Place the dried Cu(OH)2NW sample in step (6) into a tube furnace, introduce argon-hydrogen mixed gas (4% hydrogen), and heat at 4°C min -1 The temperature was raised to 380°C at a rate of 1.5 °C and maintained for 1.5 h. After natural cooling, a copper nanowire array with reduced surface was obtained, and the sample was recorded as CuNW.

[0049] Step (7) In the magnetron sputtering machine, the CuNW sample is fixed on the sample stage to form a sputtering substrate, and the sample substrate speed is 18 rmin. -1 (RPM) to ensure sputtering uniformity, a polysilicon target was placed at the RF power target position with an operating power of 80W, and a graphite target was placed at the DC power target position with an operating power of 40W. The sputtering chamber was evacuated to 5E-4Pa, and high-purity argon was introduced until the pressure was 0.4Pa, and pre-sputtering was performed for 2 minutes. During the formal sputtering, the RF target worked for 0.8h, and then the DC target worked for 25min. The sample was recorded as CuNW@Si@C;

[0050] Step (8) annealing the sample CuNW@Si@C obtained in step (7) in an argon environment of a sputtering chamber at 4°C min -1 The temperature was raised to 350°C at a rate of 2000 ℃ and then naturally cooled to 20°C to obtain a Cu3Si alloy nanowire array, and the sample was recorded as CuNW@Si@C.

[0051] Example 3

[0052] Step (1) Select a copper sheet with a circular shape, a thickness of 8 μm, and a diameter of 10 mm, and ultrasonically clean the copper sheet with dilute hydrochloric acid, deionized water, acetone, and anhydrous ethanol in sequence, and dry it for later use;

[0053] Step (2) Prepare 1.2 mol L -1 of potassium hydroxide solution;

[0054] Step (3) The constant voltage source is set to an output voltage of 1.4 V, the copper sheet dried in step (1) is connected to the anode of the voltage source, and a platinum electrode is connected to the cathode of the voltage source;

[0055] Step (4) placing the copper sheet and platinum electrode of the voltage source cathode and anode into the potassium hydroxide solution prepared in step (2) for anodic oxidation for 12 minutes, and forming a dense and uniform copper hydroxide nanowire array on the surface, and the sample is recorded as Cu(OH)2NW;

[0056] Step (5) remove the Cu(OH)2NW from the potassium hydroxide solution, rinse with deionized water, and dry for later use;

[0057] Step (6) Place the dried Cu(OH)2NW sample in step (6) into a tube furnace, introduce an argon-hydrogen mixed gas (hydrogen 6%), and heat at 6°C min -1 The temperature was raised to 420°C at a rate of 1.5 °C and maintained for 2.5 h. After natural cooling, a copper nanowire array with reduced surface was obtained, and the sample was recorded as CuNW.

[0058] Step (7) In the magnetron sputtering machine, the CuNW sample is fixed on the sample stage to form a sputtering substrate, and the sample substrate speed is 22 rmin. -1 (RPM) to ensure sputtering uniformity, a polysilicon target was placed at the RF power target position with an operating power of 120W, and a graphite target was placed at the DC power target position with an operating power of 60W. The sputtering chamber was evacuated to 5E-4Pa, and high-purity argon was introduced until the pressure was 0.4Pa, and pre-sputtering was performed for 4 minutes. During the formal sputtering, the RF target worked for 1.2 hours, and then the DC target worked for 35 minutes. The sample was recorded as CuNW@Si@C;

[0059] Step (8) annealing the sample CuNW@Si@C obtained in step (7) in an argon environment of a sputtering chamber at 6°C min -1 The temperature was raised to 450°C at a rate of 200 °C and then naturally cooled to 30°C to obtain a Cu3Si alloy nanowire array, and the sample was recorded as CuNW@Si@C.

[0060] Obviously, the above embodiments are merely examples for clear explanation and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the protection scope of the invention.

Claims

1. A method for preparing a lithium-ion battery silicon negative electrode with an alloyed array transition layer optimized, characterized in that: The steps include: S11: connecting the pretreated copper sheet to the anode of a voltage source, connecting the platinum electrode to the cathode of a voltage source, and oxidizing the copper sheet in an aqueous solution of potassium hydroxide for 8-12 minutes to obtain a copper hydroxide nanowire array; S12: washing the copper hydroxide nanowire array with water and then drying it to obtain a Cu(OH)2NW sample; S13: In an argon-hydrogen mixed atmosphere, the Cu(OH)2NW sample is heated to 380-420° C. and kept at this temperature for 1.5-2.5 h, and then cooled to obtain a CuNW sample; S14: Under a protective atmosphere, magnetron sputtering the CuNW sample with a radio frequency power target for 0.8-1.2 hours, and then magnetron sputtering with a direct current target for 25-35 minutes to obtain a CuNW@Si@C sample; the radio frequency power target is selected from a polycrystalline silicon target, and the direct current target is selected from a graphite target; S15: annealing the CuNW@Si@C sample under a protective atmosphere to obtain the lithium-ion battery silicon negative electrode with the alloyed array transition layer optimized.

2. The preparation method according to claim 1, characterized in that In the step S11, the copper sheet is pretreated by ultrasonically cleaning with hydrochloric acid, water, acetone, and ethanol in sequence, and then drying.

3. The preparation method according to claim 1, characterized in that: The potassium hydroxide aqueous solution has a concentration of 0.8-1.2 mol L -1 .

4. The preparation method according to claim 1, characterized in that: In the step S11, the output voltage of the voltage source during oxidation is 1-1.4V.

5. The preparation method according to claim 1, characterized in that: In the argon-hydrogen mixed atmosphere, the volume proportion of hydrogen is 4-6%.

6. The preparation method according to claim 1, characterized in that: In step S13, the heating rate is 4-6°C / min.

7. The preparation method according to claim 1, characterized in that: In the step S14, during magnetron sputtering, the substrate rotation speed is 18-22 rpm, the working power of the RF power target is 80-120 W, and the working power of the DC target is 40-60 W.

8. The preparation method according to claim 1, characterized in that: In the steps S14 and S15, the protective atmosphere is an argon atmosphere.

9. The preparation method according to claim 1, characterized in that: In the step S15, the annealing method is to heat up to 350-450°C and then naturally cool to room temperature; during annealing, the heating rate is 4-6°C / min.

10. A lithium-ion battery silicon negative electrode with an optimized alloyed array transition layer prepared by the preparation method according to any one of claims 1 to 9.

Citation Information

Cited By

  • Composite material, preparation method of composite material and battery

    CN121641897A